Dignitas Perpetua: The Sacerdotal and Sacramental Constitution of The Person - Croitoru, Mihai Marian (Technium Social Sciences Journal, 2023)
The connection with all that exists can and should be a liturgical and thankful connection, imprinted by God's love for us. The liturgical aspect can be observed not only in the concrete ecclesial context, but also in the social one, in the ratio of the need for the life of the Church and the desire to receive it in the world at different levels. The liturgical ministry itself, which gives us through the One whom we serve the liturgical power, sends us to a continuous ministry, showing that I am capable of tirelessly realizing myself as a man who understands service from all its angles.